2020
DOI: 10.1002/acr.24032
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Caregiver Priorities for Medication Adherence in Gout, Osteoporosis, and Rheumatoid Arthritis: Nominal Group Technique

Abstract: Objective This study aimed to identify and prioritize factors important to patients and caregivers with regard to medication adherence in gout, osteoporosis (OP), and rheumatoid arthritis (RA) and to describe the reasons for their decisions. Methods Patients with gout, OP, and RA and their caregivers, purposively sampled from 5 rheumatology clinics in Australia, identified and ranked factors that they considered important for medication adherence using nominal group technique and discussed their decisions. An … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 44 publications
2
13
0
Order By: Relevance
“…In absence of other reports on the relationship of BMQ with treatment success in gout, we assume that information on dose adjustment in ULT would motivate and convince patients to take their medication and therefore improve adherence to ULT. 37 Qualitative research has also shown that trust in doctor and medication effectiveness were identified as the most important factors for adherence, 38 indicating that thorough information and personal contact with the health provider could improve medication compliance.…”
Section: Discussionmentioning
confidence: 99%
“…In absence of other reports on the relationship of BMQ with treatment success in gout, we assume that information on dose adjustment in ULT would motivate and convince patients to take their medication and therefore improve adherence to ULT. 37 Qualitative research has also shown that trust in doctor and medication effectiveness were identified as the most important factors for adherence, 38 indicating that thorough information and personal contact with the health provider could improve medication compliance.…”
Section: Discussionmentioning
confidence: 99%
“…A recent focus group study, including patients in Australia with gout, osteoporosis and rheumatoid arthritis, and their caregivers, identified that trust in the physician, physician’s knowledge, and medication properties (e.g., effectiveness and side effects) were important factors contributing to medication adherence. The authors of the study highlighted that increased trust and knowledge exchange between doctors and patients could improve medication adherence [ 23 ]. A focus group study including 30 inpatients from four Australian hospitals confirmed that staff–patient communication (and communication between staff members), and the sharing of high-quality information with patients and their families or carers, are important for patient satisfaction [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Effective communication about beliefs about medication and adherence starts with facilitating and being aware of the patient's knowledge about medication. Several studies describe the importance of this knowledge for medication adherence 32,38 . To improve adherence, misconceptions about illness and treatment should be avoided by exploring, understanding and engaging with a patient's knowledge and ideas about causality, experiences of symptoms and concerns about treatment 39–41 …”
Section: Discussionmentioning
confidence: 99%
“…Another part of effective communication is creating a setting in which patients feel safe to raise their beliefs about medication and to speak out about medication nonadherence, so that nonadherence will not remain a hidden problem 38,42 . Finally, patients should be encouraged to raise issues concerning beliefs about medication and nonadherence in patient‐HCP interactions.…”
Section: Discussionmentioning
confidence: 99%